DEVONIAN OF NORTHEASTERN ASIA - Gagiev M.H. (My University, 2001)
In the Devonian series of northeastern Asia all standard stage boundaries are recognised using conodont indexes, as well as guides as guides of other fossil groups. Other potential correlation means include event boundaries which show characteristic sedimentologic features, and which reveal worldwide faunistic changes.
Keywords: Devonian; Northeastern Asia; conodont indexes; Paleozoic::Devonian; Палеозой::Девонская